Salicylaldoxime-functionalized poly(ethylene glycol)-grafted dicationic ionic liquid as a water-soluble and recyclable ligand for palladium-catalyzed Mizoroki–Heck reactions in aqueous phase. Issue 9 (3rd May 2017) - Wang, Yinglei; Liu, Xueguo; Du, Chaojun; Zhang, Li
ABSTRACT: A water-soluble salicylaldoxime-functionalized poly(ethylene glycol)-grafted dicationic ionic liquid was successfully developed as an efficient ligand for palladium acetate-catalyzed Mizoroki–Heck reactions in water. A series of aryl bromides and terminal olefin were applied to this catalytic system and the corresponding coupling products were produced in high yields. The reusability tests demonstrated that the catalyst system could be recycled for six runs with only a slightly decreased activity. GRAPHICAL ABSTRACT: